A Educação Ambiental na Rede Municipal de Ensino de Ibaté - SP: os desafios e as dificuldades de sua implementação - Fachina, Stefania (Universidade Federal de São Carlos, 2019)
The purpose of this Masters Dissertation is to analyze if the Environment Education Program it is, in fact, implemented into the city of Ibate’s (State of San Paulo) municipal education system, using as a reference the investigation of the Municipal Law n° 2.554/2010, which constitutes the Municipal Policy of the Environment Education Program, with the intention of verifying if there is correspondence between the ordered by law and the one fulfilled by the educational agents. For the analysis, a research roadmap was developed with questionnaires and interviews for the municipal teachers, which made it possible to identify that the Environment Education Program, although present in the discourses, it does appear in specific situations of the pedagogical practice. It is also occasionally related to municipal regulations, which compromises the complete execution of the law and important precepts of the Environment Education Program. The Research Roadmap was characterized as a research and investigation tool for the strengthening and reflection of Environment Education Program in the school spaces. Thus, the study points out the need to reformulate the teacher’s perceptions for critical Environment Education and the necessity of ongoing training of environmental educators by municipal public bodies.
Keywords: Educação ambiental; Política Municipal de Educação Ambiental; Professores; Rede Municipal de Ensino; Ibaté (SP); Environmental education; Municipal Policy of the Environment Education Program; Teachers; Municipal Education System; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ORIENTACAO E ACONSELHAMENTO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO